Adaptation and validation of the financial stress scale in social conflict contexts: a study conducted with small and medium-sized Peruvian entrepreneurs - Tito-Betancur, Madona; Huayta-Meza, Mariné; Chaparro, Josué Turpo; Morales-García, Wilter C.; Mamani-Benito, Oscar (Frontiers in Psychology, 2023)
Introduction: Social conflicts have repercussions on the mental health of the economically active population. Objective: To adapt and validate the Financial Stress Scale in the context of social conflicts (ESECPS). Method: An instrumental study involving 2,242 owners of small and medium enterprises (50.9% women), aged between 18 to 74 years old, selected through a non-probabilistic purposive sampling. The participants were recruited across three regions of Peru during periods of protests and strikes against the incumbent Peruvian government. The instrument for adaptation was the financial stress scale EFEmp-Cov19, created in the context of the COVID-19 pandemic's impact. Results: All items proved to be clear, relevant, and representative (V > .70). Exploratory Factor Analysis (EFA) revealed the existence of one underlying factor across the 11 items (KMO = 0.962, Bartlett = 5434.3; df = 55; p < 0.001). However, for Confirmatory Factor Analysis (CFA), items 4 and 11 were removed, resulting in support for a unidimensional model with 9 items (χ2 = 262.73, df = 23, p < .001; RMR = .022; TLI = .972; CFI = .980; and RMSEA = .072). Regarding reliability, a very high value was found (ω = .92). Conclusion: The ESECPS demonstrates adequate psychometric properties, making it a suitable measure to assess financial stress among Peruvian entrepreneurs facing economic instability and financial threats in the context of social conflicts.